2021
DOI: 10.1093/molbev/msab065
|View full text |Cite
|
Sign up to set email alerts
|

Limited Predictability of Amino Acid Substitutions in Seasonal Influenza Viruses

Abstract: Seasonal influenza viruses repeatedly infect humans in part because they rapidly change their antigenic properties and evade host immune responses, necessitating frequent updates of the vaccine composition. Accurate predictions of strains circulating in the future could therefore improve the vaccine match. Here, we studied the predictability of frequency dynamics and fixation of amino acid substitutions. Current frequency was the strongest predictor of eventual fixation, as expected in neutral evolution. Other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…However, the pace of antigenic selection varies over time for influenza A virus (IAV) subtypes and influenza B virus (IBV) lineages due mainly to population-level fluctuations in immune pressure. This confounds vaccine strain selection, which relies on the prediction of antigenic evolution 3 . To facilitate bi-annual selection of candidate vaccine viruses, the WHO Global Influenza Surveillance and Response System (GISRS) coordinates influenza surveillance from 138 National Influenza Centers (NICs) and diagnostic and reference laboratories in 108 countries 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the pace of antigenic selection varies over time for influenza A virus (IAV) subtypes and influenza B virus (IBV) lineages due mainly to population-level fluctuations in immune pressure. This confounds vaccine strain selection, which relies on the prediction of antigenic evolution 3 . To facilitate bi-annual selection of candidate vaccine viruses, the WHO Global Influenza Surveillance and Response System (GISRS) coordinates influenza surveillance from 138 National Influenza Centers (NICs) and diagnostic and reference laboratories in 108 countries 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, Barrat-Charlaix et al. ( 50 ) found that mutations at the epitope sites in ( 36 ) fixed in the population less often than would be expected under neutral drift.…”
Section: Resultsmentioning
confidence: 99%
“…Barrat-Charlaix et al. ( 50 ) recently found that consensus strains are as close or closer to future populations than strains with a high local branching index, motivating the comparison to consensus strains. Figure 5 shows the epitope and amino acid distances (epitope site–only amino acid Hamming distance and whole-sequence amino acid Hamming distance, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…A question of interest in applications is whether a newly appeared mutation is likely to sweep over the population. Think, for instance, in seasonal flu vaccine planning, where interest lies in predicting the most prevalent genetic variant a year ahead of time, so that effective vaccines can be designed before the next season, see, e.g., [3], [4], [5], [6]. In order to study deviations from neutrality, accurate inferences on are needed.…”
Section: Introductionmentioning
confidence: 99%